Dynamic coronary roadmap in percutaneous coronary intervention: a systematic review and meta-analysis - Amir Hossein Behnoush; Alireza Ramandi; Sugandhi Mahajan; Ahmed Altibi; Amirsaeed Samavarchitehrani; Rahul Gupta (BMC Cardiovascular Disorders)
Abstract Background Contrast-induced acute kidney injury (CI-AKI) is one of the complications of percutaneous coronary intervention (PCI) with high financial burden and poor outcomes. Dynamic coronary roadmap (DCR) is one of the augmentation tools that can provide a dynamic clear coronary mapping with the potential to reduce contrast use and CI-AKI incidence. Herein, we aim to systematically investigate the studies that have assessed the effect of DCR on PCI outcomes. Methods Four online databases including PubMed, Scopus, Embase, and the Web of Science were systematically searched for relevant studies. Studies that compared the DCR group with the non-DCR group were included while the outcomes were AKI incidence, contrast volume, fluoroscopy time, dose area product, air kerma, intravascular ultrasonography (IVUS) use, and procedural success. Random-effect meta-analysis was conducted to calculate the standardized mean difference (SMD) or odds ratio (OR) and 95% confidence interval (CI) for comparison of DCR and non-DCR groups. Results A total of six studies were included in the final analysis comprised of 447 patients in the DCR group and 527 in the non-DCR group. The mean age was 68.7 ± 10.6 years while 78.9% of the DCR group and 75.6% of the non-DCR group were males. There was no difference between the groups in terms of the rates of hypertension, diabetes, hyperlipidemia, prior myocardial infarction (MI), prior coronary artery bypass grafting (CABG), and atrial fibrillation. Meta-analysis revealed that patients in the DCR group had a significantly lower rate of AKI (OR 0.50, 95% CI 0.27 to 0.93, p-value = 0.028), and contrast volume used (SMD -1.16, 95% CI -2.15 to -0.18, p-value = 0.021). However, there was no difference in fluoroscopy time (SMD -0.64, 95% CI -1.43 to 0.16, p-value = 0.116), air kerma (SMD -1.81, 95% CI -4.61 to 0.99, p-value = 0.206), IVUS use (OR 1.21, 95% CI 0.85 to 1.73, p-value = 0.285), and procedural success (OR 1.05, 95% CI 1.15 to 7.26, p-value = 0.957). Conclusion These findings show that DCR use is associated with a lower rate of AKI and lower contrast use, compared to conventional PCI. This is of particular importance since many patients undergoing PCI have limited renal function and hence will benefit from the use of DCR. Further studies are needed to confirm these findings and to pave the way for the routine use of DCR in clinical settings.